Association of Mutation and Polymorphism in Lipoprotein Lipase Gene with Coronary Heart Disease in Some Iraqi Patient - Rasheid, Abduqader W. (Indonesian Journal Publisher, 2025)
Prior research has assessed the correlations between the likelihood of acquiring diabetes mellitus and the polymorphism in the cholesterol ester transfer protein (LIPASE GENE). Chronic hyperglycemia and abnormalities in the metabolism of carbohydrates, fats, and proteins due to deficiencies in insulin production, action, or both are characteristics of the metabolic condition known as diabetes mellitus (DM), which has several etiologies. However, the conclusions are still up for debate. This study sought to determine whether lipid profile abnormalities in Iraqi diabetic patients were associated with the LIPASE GENE. Methods, To shed light on the relationships between the LIPASE GENE TaqIB polymorphism, HDL-C levels, and diabetes mellitus, we performed a meta-analysis of the literature. Findings: This study included 160 Iraqi participants, 90 of whom had diabetes mellitus, and 70 of whom served as controls. Table 1 displays the population study's blood lipid data. TC, TG, LDL-C, and VLDL-C were all considerably greater (P<0.0001) in the patient group than in the control group, with the exception of HDL-C, which was lower (P<0.0001). In this study, there were more men (75.55%) than women (24.4%) with type 2 diabetes. The large percentage of men in this research may result from the demographics of the hospital's patients, who tend to seek medical care more frequently than women to have more free time because most of them are retired. Included in the correlation between HDL-C concentration and lipase polymorphism. The LIPASE GENE gene has been shown to have a variety of single nucleotide polymorphisms. The influence of the rs708272 (g.5454G>A) polymorphism on HDL-C focus has been explained. This study aimed to evaluate the LIPASE gene site polymorphism and its effect on blood lipids in Iraqi patients with lipid problems. Since a few evaluations listed the LIPASE GENE polymorphism's association with the HDL level we decided to use it because we couldn't locate any Iraqi studies that addressed this polymorphism.